The impersonal construction in Manipuri (Meithei) - Singh, Chungkham Yashawanta (2024)
The grammar of a particular language can be regarded as simply a specification of values of parameters of Universal Grammar (Chomsky 1981). It is the general notion among linguists dealing with "language universals" that the subject-predicate relationship is one among the several parameters of language universals. In most languages "subject" generally occurs initially in a syntactic construction.' In other words, in most languages subject precedes the other major NPs within clauses. Secondly, the predicate, in general, is bound to the subject in terms of one or more grammatical categories, such as gender, number, person, case, or voice, with varying degrees of involvement of them.